Pyrolysis-derived recovered glass fiber-engineered ultrafiltration membrane for dyeing wastewater treatment - Fengzhi Guo; Haolun Wang; Fan Shao; Jinzhi Jiang; Guorui Li; Xinmeng Ma; Haoran Ma; Keyi Li; Lu Gong; Yue Ma; Changtao Yue (Chemical Engineering Journal, 2026)

Imidazolium salt-functionalized Cu2O@SiO2 catalysts for integrated CO2 capture and electroreduction to multi-carbon products in acidic electrolytes - Hui Zhang; Shanshan Lou; Fan Yang; Keyi Fan; Zhengxin Gu; Wangbo Li; Yihe Chen; Yizhen Gan; Lushan Ma; Guoliang Wang; Hui Yang (Chemical Engineering Journal, 2025)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

High nutrient utilization and resorption efficiency promote bamboo expansion and invasion - Keyi Zuo; Lili Fan; Ziwu Guo; Le Zhang; Yiyang Duan; Jingrun Zhang; Shuanglin Chen; Hua Lin; Ruicai Hu (Journal of Environmental Management, 2024)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

Motion behavior of non-Newtonian fluid-solid interaction foods - Yuhe Fan; Lixun Zhang; Canxing Zheng; Xingyuan Wang; Keyi Wang; Jinghui Zhu (Journal of Food Engineering, 2023)

Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.

Short-term effects of ambient particulate matter (PM1, PM2.5 and PM10) on influenza-like illness in Guangzhou, China - Jianyun Lu; Keyi Wu; Xiaowei Ma; Jing Wei; Zelin Yuan; Zhiwei Huang; Weidong Fan; Qi Zhong; Yining Huang; Xianbo Wu (International Journal of Hygiene and Environmental Health, 2023)

RNA-seq Provides Novel Insights into Response to Acute Salinity Stress in Oriental River Prawn Macrobrachium nipponense - Yaoran Fan; Jianbin Feng; Nan Xie; Feiyue Ling; Zefei Wang; Keyi Ma; Xueming Hua; Jiale Li (Marine Biotechnology, 2022)

Cloning and expression analysis of juvenile hormone epoxide hydrolase-like ( EsJHEH-like ) from Eriocheir sinensis , and its potential roles in methyl farnesoate metabolism - Tiantian Chen; Yingzhu Diao; Ruihan Xu; Na Sheng; Fan Liu; Qiming Xie; Shiping Su; Keyi Ma; Xilei Li (Invertebrate Reproduction & Development, 2022)